2008
DOI: 10.1080/08982110802334104
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Directionally Sensitive MCUSUM and MEWMA Procedures with Application to Biosurveillance

Abstract: This paper compares the performance of two new directionally-sensitive multivariate methods, based on the multivariate CUSUM (MCUSUM) and the multivariate exponentially weighted moving average (MEWMA), for biosurveillance. While neither of these methods is currently in use in a biosurveillance system, they are among the most promising multivariate methods for this application. Our analysis is based on a detailed series of simulations using synthetic biosurveillance data that mimics various types of disease bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Jackson et al 37 compared the performance of EMWA, Shewhart chart, and a general linear model method based on the data set having day-of-the-week effects. Because of the spatiotemporal characteristics of biosurveillance data, modifications of the multivariate SPC techniques such as MCUSUM and MEWMA have been suggested by Joner et al 35 and Fricker et al 38 Comprehensive review of the applications of SPC methods to health surveillance can be found in Woodall 1 and Tsui et al 4 .…”
Section: Introductionmentioning
confidence: 98%
“…Jackson et al 37 compared the performance of EMWA, Shewhart chart, and a general linear model method based on the data set having day-of-the-week effects. Because of the spatiotemporal characteristics of biosurveillance data, modifications of the multivariate SPC techniques such as MCUSUM and MEWMA have been suggested by Joner et al 35 and Fricker et al 38 Comprehensive review of the applications of SPC methods to health surveillance can be found in Woodall 1 and Tsui et al 4 .…”
Section: Introductionmentioning
confidence: 98%
“…Often the goal in applications such as biosurveillance is to detect "signed" change, such as increases in reported incidents of an infectious disease. Although several approaches to developing directionally sensitive multivariate procedures have been considered (Fricker 2007;Fricker, Knitt, and Hu 2008;Joner et al 2008), existing graph-theoretic procedures are not designed for this setting.…”
Section: Future Workmentioning
confidence: 99%
“…We assume that such systematic components of the data can be appropriately modeled and thus accounted for and removed from the data. See, for example, Fricker et al [12,13] where adaptive regression was used to remove the systematic effects from syndromic surveillance data. We then assume that the Shewhart charts are used to monitor the standardized residuals from such a model and that the residuals can be assumed to be independently distributed according to a standard normal distribution.…”
Section: The Biosurveillance Problemmentioning
confidence: 99%